Blockchain technology can improve food supply chain security - Mimi Rabita, Abdul Wahit; Siti Nurfarmy, Ibrahim (2020)
PEKAN, 24 December 2020 - Integrity and traceability systems in the food supply chain are very important in ensuring the safety of the food supply chain so that consumers get good and halal food products.